2022
DOI: 10.1093/brain/awac342
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of YAP/TAZ-driven TEAD activity prevents growth of NF2-null schwannoma and meningioma

Abstract: Schwannoma tumours typically arise on the 8th cranial nerve and are mostly caused by loss of the tumour suppressor Merlin (NF2). There are no approved chemotherapies for these tumours and the surgical removal of the tumour carries a high risk of damage to the 8th or other close cranial nerve tissue. New treatments for schwannoma and other NF2-null tumours such as meningioma are urgently required. Using a combination of human primary tumour cells and mouse models of schwannoma, we have examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Such arrangement can lead to changes in the nuclear to cytoplasmic connections and facilitate the aberrant transport of nuclear effector/oncogenes in the NF2 mutant background. One such example is the protein YAP, which is known to aid NF2- mediated tumorigenesis (Guerrant et al, 2016; Laraba et al, 2022; Oh et al, 2015; Szulzewsky et al, 2022). While several studies have explored the functional role of YAP in combination with NF2 in tumorigenesis, the mechanobiological aspect of their interaction is yet to be decoded.…”
Section: Discussionmentioning
confidence: 99%
“…Such arrangement can lead to changes in the nuclear to cytoplasmic connections and facilitate the aberrant transport of nuclear effector/oncogenes in the NF2 mutant background. One such example is the protein YAP, which is known to aid NF2- mediated tumorigenesis (Guerrant et al, 2016; Laraba et al, 2022; Oh et al, 2015; Szulzewsky et al, 2022). While several studies have explored the functional role of YAP in combination with NF2 in tumorigenesis, the mechanobiological aspect of their interaction is yet to be decoded.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of NF2 results in deregulation and activation of oncogenic YAP activity and increased levels of YAP activity have been observed in NF2 mutant over NF2 wild type meningiomas 11,12 . Oncogenic YAP activity has also been implicated in the pathobiology of other tumors harboring inactivating NF2 mutations [44][45][46][47] . We have previously shown that the expression of an oncogenic point mutant YAP construct is able to induce the formation of meningioma-like tumors in mice 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancement has been made in the search for novel therapeutic approaches to treat meningiomas. Studies have demonstrated that blocking the interaction between YAP1 and TEAD or targeting TEAD auto-palmitoylation can effectively inhibit tumor formation and suppress tumor growth in the YAP1 fusion/ NF2 mutant meningioma and schwannoma [ 15 , 20 , 21 ]. However, the number of reported YAP1 fusion meningioma cases remains limited.…”
Section: Discussionmentioning
confidence: 99%